Comparison of two methods of protein quality evaluation in rice, rye and barley as food protein sources in human nutrition - Soňa Nitrayová (Potravinarstvo, 2018)
Different foods differ in their protein quality, which is characterized by the content and digestibility of individual amino acids. The Food and Agriculture Organisation has recommended replacing the method for protein quality evaluation of foods called protein digestibility corrected amino acid score (PDCAAS) with the new method - digestible indispensable amino acid score (DIAAS), in which the values of ileal amino acid digestibility obtained in pigs are used. However, the information about DIAAS values of foods are limited. Therefore, the study on growing pigs was conducted to determine true fecal protein digestibility and standardized ileal amino acid digestibility of rice, rye and barley. Using these values, the PDCAAS and DIAAS were calculated and compared. A total of 18 gilts with a T-cannula inserted in the terminal ileum were allotted to 3 diets with six replicate pigs per diet. Three semi-purified diets were formulated to contain the tested cereal grains (rice, rye, barley) as the sole nitrogen source. Chromic oxide was used as indigestible marker. Each experimental period comprised of a 7-d adaptation period followed by 24 h collection of feces and ileal digesta. The content of nitrogen, dry matter and chromic oxide was analyzed in samples of diets, feces and ileal digesta. Moreover, in the samples of diets and ileal digesta the content of amino acids was determined. Calculated ratio of crude protein to lysine was greatest in rice (4.50) followed by rye (3.65) and the lowest one in barley (3.35). True fecal protein digestibility was greater when compared with ileal amino acid digestibility for all tested samples, thus suggesting an overestimation of protein quality determined by PDCAAS. Calculated PDCAAS values for rice, rye and barley (81, 65 and 61%) were generally greater than the DIAAS values (79, 56 and 55%), especially for the poorer quality protein sources such as rye and barley in comparison with rice. The lysine was the first limiting amino acid in all tested cereal grains. Based on the DIAAS evaluation, rice is better protein source in human nutrition in comparison with rye or barley.